Energy storage component and method thereof. - Shaari, Abdul Halim; Primus, Walter Charles; Wan Yusoff, Wan Mohd Daud; Talib, Zainal Abidin; Saion, Elias (2009)

(untitled)
The present invention is a new composition of matter and can be used as components of a capacitor. The dielectric properties possess in this material has improved tremendously as compared to the existing component. The finding of high dielectric permittivity in the present compared to the existing component. The finding of high dielectric permittivity in the present invention ceramic according to its formulation and processing technique that can operate or use at wide range frequencies and temperatures are very useful in electronic and electrical device. The present invention is best for application at the range of temperatures. the permittivity is recorded at 1kHz are between 20,000 to 54,000 and almost constant over three decade of frequency. Thus, the dielectric permittivity obtained can be used as energy storage, sensor, electric filter, etc., besides minimizing the devices.